The ethnobotany of honey-based plant remedies: A systematic review of Plant–Honey–Human Therapeutic Interactions - Ouaamr, Ahmed; El Yaagoubi, Mohamed; Takhdat, Kamal; Arzoug, Hafid; Alaoui, Katim (Ethnobotany Research and Applications, 2026)
Background: Honey is widely used in traditional medicine, but often as a carrier and therapeutic matrix for medicinal plants rather than as a standalone agent. Despite the recurrence of these combinations in ethnobotanical literature, their diversity, indications, dosage forms, and level of scientific validation have not been synthesized systematically. Methods: Following PRISMA 2020, we searched Scopus, Web of Science Core Collection, PubMed/MEDLINE, ScienceDirect, and Google Scholar from database inception to 31 December 2025 for peer-reviewed studies reporting traditional use or experimental/clinical evaluation of remedies combining honey with medicinal plants. Ethnobotanical, experimental, and clinical studies in English or French were eligible. Data were extracted on geography, taxa, plant parts, preparation forms, indications, and level of evidence. Because of heterogeneity, findings were synthesized narratively. Results: Thirty-four studies met the inclusion criteria. They reported 79 plant species in 42 families, with strongest representation from North Africa and the Middle East and from South and Southeast Asia. Frequently cited taxa included Nigella sativa, Zingiber officinale, Allium sativum, Thymus vulgaris, Curcuma longa, and Eucalyptus globulus. Main dosage forms were powder-honey mixtures, syrups, macerations, and medicinal pastes. Respiratory disorders, gastrointestinal complaints, and wound or skin conditions were the dominant therapeutic categories. More than half of the included studies reported experimental or preclinical support, whereas clinical evidence remained limited. Conclusions: Honey-based plant remedies may be interpreted as part of a broader biocultural therapeutic framework shaped by the interaction between plant metabolites, honey as a therapeutic matrix, and locally transmitted medical knowledge. Recurrent plant-honey combinations provide priority leads for phytochemical standardization, pharmacological testing, and future clinical evaluation. Keywords: apitherapy; ethnobotany; ethnopharmacology; honey; medicinal plants; traditional medicine; honey-based plant remedies; systematic review